Microlearning: possibilidades e desafios na educação corporativa - Alves, Marissol Mello (2020)
The contemporary professional finds himself immersed in many challenges having to deal with an infinite amount of distractions and interruptions, at the same time that he is exposed to all kinds of stimuli resulting from the interaction with the digital environment. Employers, on the other hand, need to continually requalify their workforce to keep pace with changes - being able to use their learning and development (L&D) area as a strategic tool. L&D professionals, who are responsible for corporate training within their companies, are constantly looking for innovative solutions that can be efficient in these scenarios. Although the Brazilian L&D market is structured, it is still inspired by trends that initially emerge in more mature markets, such as the American or European, where the microlearning theme gained visibility a few years ago. Even though micro-learning has frequently appeared in the commercial portfolio of corporate education providers, as a solution to modern problems, the scientific and academic material on the subject, mainly in the national language, is reduced, therefore justifying this research, presenting an opportunity to explore and deepen the theme: microlearning - as its possibilities and its challenges. Thus, this research has a general objective, examining specific characteristics of microlearning, extracting from the current literature concepts that can converge in a consistent definition. It also brings as specific objectives, mapping the available body of knowledge from academic researchers regarding the subject in the period from January 2015 to July 2019, identifying similarities between these academics and publications coming from the L&D industry seeking a convergent perspective that can offer subsidies for critical analysis by L&D professionals and, finally, to bring a look at the perception of some L&D professionals from the Brazilian industry regarding the adoption of microlearning, through the collection of data over an online questionnaire. This research is, therefore, an exploratory investigation that seeks to identify, subsidize and confront with the theory the hypotheses and practices detected concerning microlearning format as an alternative for the delivery of educational content, potentially coming to serve as a support in the autonomous evaluation by the professionals working the L&D area. This research also proposes to investigate theoretical foundations that support microlearning as a viable option for corporate education, presenting in its theoretical framework the studies from andragogy (KNOWLES, LINDEMAN), heutagogy (HASE, KENYON) and connectivism (SIEMENS), as well as the structures on didactics of microlearning (HUG). As obtained results, this research presents concepts that can contribute with the T&D professional with subsidies supporting critical and autonomous analyzes in the face of an innovative proposal focusing on corporate education, as well as shares a perspective of the stage of maturity and readiness for the adoption of microlearning in Brazil